Isolation and characterization of cold sensitive pex6 mutant of the methylotrophic yeast Hansenula polymorpha - Nazarko, V. Y.; Pochapinsky, O. D.; Nazarko, T. Y.; Stasyk, O. V.; Sibirny, A. A. (Біополімери і клітина, 2002)
A cold sensitive (cs) suppressor mutant was isolated from the H. polymorpha pex6 strain defective in peroxisome biogenesis. The restored cs pex6 growth on methanol at a permissive temperature was associated with the presence of morphologically normal peroxisomes. The enlarged peroxisomes present at restrictive temperature failed to support methylotrophic growth in the cs pex6 strain. The isolated mutation has no effect on the peroxisome degradation in H. polymorpha. Виділено холодочутливий супресорний мутант зі штаму рех6 Н. polymorpha з пошкодженим біогенезом пероксисом. Відмовлення росту холодочутливого рех6 на метанолі при пермісивній температурі корелювало з наявністю морфологічно нормальних пероксисом. Збільшені у розмірах пероксисоми при рестриктивній температурі не здатні підтримувати метилотрофний ріст холодочутливого штаму рех6. Виділена мутація не впливає на деградацію пероксисом Н. polymorpha. Выделен холодочувствительный супрессорный мутант на основе штамма рех6 Н. polymorpha с поврежденным биогенезом пероксисом. Восстановление роста холодочувствительного рех6 на метаноле при пермиссивной температуре коррелировало с наличием морфологически нормальных пероксисом. Увеличенные в размерах пероксисомы при рестриктивной температуре не способны поддерживать метилотрофный рост холодочувствительного штамма pex6. Выделенная мутация не влияет на деградацию пероксисом Н. polymorpha.